Pengaruh Literasi, Religuisitas dan Pendapatan Terhadap Kepatuhan Muzakki dalam Membayar Zakat Pertanian di Daerah Bogor: BAZNAS KAB.BOGOR - Olivia Widyasari Irsanti; Mohammad Bintang Pamuncak (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The National Amil Zakat Agency proposed the establishment of the Mustahik Economic Empowerment Agency as a solution. This organization is tasked with improving the quality of life of the beneficiaries through its programs. The purpose of this study is to examine the impact of literacy, religiosity, and income on agricultural zakat compliance in Bogor Regency. Study utilizes quantitative data from survey conducted on all Muslims who meet zakat nisab in Bogor City. A purposive sampling technique was used in selecting the research sample of 110 respondents. After the questionnaire has been validated, the data was collected and then analyzed using SMART PLS method. The analysis proves that literacy (X1), religious level (X2), and income (X3) have a significant effect on compliance (Y) of muzakki in paying agricultural zakat.